Making history happen: a genealogical analysis of Colt's rhetorical history. Issue 2 (2nd April 2016) - Poor, Stephen; Novicevic, Milorad M.; Humphreys, John H.; Popoola, Ifeoluwa Tobi
Abstract: The rugged and individualistic reputation of Samuel Colt and the Colt Company is the stuff of legend in the American psyche. Largely constructed from themes aligned with American exceptionalism and the taming of the Western frontier, this firearm maker built a powerful and pervasive image. In this study, we examine how the Colt Company used rhetorical history in an agentic, proactive way to appropriate history and tradition for strategic purposes. Specifically, we apply a genealogical method to analyze the ways that rhetorical history was used by Colt in order to augment our understanding of rhetorical history and its utilization as a competitive image-enhancing practice.